Innate Recognition of Pheromone and Food Odors in Moths: A Common Mechanism in the Antennal Lobe? - Martin, Joshua P.; Hildebrand, John G. (Frontiers in Behavioral Neuroscience, 2010)
The survival of an animal often depends on an innate response to a particular sensory stimulus. For an adult male moth, two categories of odors are innately attractive: pheromone released by conspecific females, and the floral scents of certain, often co-evolved, plants. These odors consist of multiple volatiles in characteristic mixtures. Here, we review evidence that both categories of odors are processed as sensory objects, and we suggest a mechanism in the primary olfactory center, the antennal lobe (AL), that encodes the configuration of these mixtures and may underlie recognition of innately attractive odors. In the pheromone system, mixtures of two or three volatiles elicit upwind flight. Peripheral changes are associated with behavioral changes in speciation, and suggest the existence of a pattern recognition mechanism for pheromone mixtures in the AL. Moths are similarly innately attracted to certain floral scents. Though floral scents consist of multiple volatiles that activate a broad array of receptor neurons, only a smaller subset, numerically comparable to pheromone mixtures, is necessary and sufficient to elicit behavior. Both pheromone and floral scent mixtures that produce attraction to the odor source elicit synchronous action potentials in particular populations of output (projection) neurons (PNs) in the AL. We propose a model in which the synchronous output of a population of PNs encodes the configuration of an innately attractive mixture, and thus comprises an innate mechanism for releasing odor-tracking behavior. The particular example of olfaction in moths may inform the general question of how sensory objects trigger innate responses.